The Application Of Finger Grip Relaxation Therapy To Reduce Pain Level In Patient With Post-Operative Appendicitis; A Case Study - Dewi, Rini Sartiya; Wijayanti, Fitri; Putri, Putri (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
One of the treatments for appendicitis is surgery. Surgery will certainly cause post-operative pain that needs to be handled appropriately. If it is not treated immediately, pain in post-operative patients will slow down patient recovery, results in long hospitalization, prone the patient to a high complication rate, and require a lot of costs. Therefore, proper handling of post-operative pain is needed. In addition to drugs, non-pharmacological techniques can be a supportive treatment that proven to be effective. A non-pharmacological technique that can reduce pain is finger grip relaxation therapy. This study aims to describe the nursing care in a case of patient with post-operative appendicitis given finger grip relaxation therapy to reduce pain. This is a descriptive case study of an adult postoperative appendicitis patient with major nursing problems, acute pain. Results showed that the patients suffering level 6 of pain (moderate pain). The patient was given intervention including analgesic and supported with hand-held finger grip therapy in three days. The intervention was given three times a day, with a duration of 30 minutes. After given the intervention, the patient reported a decrease in pain level, into level 1 (mild pain). It can be concluded that nurses can apply finger grip relaxation therapy to provide nursing intervention or nursing care for post-operative patient to accelerate pain relief.